Perencanaan dan Perancangan Rumah Saki Ibu dan Anak Deltamas dengan Pendekatan Behaviour Architecture - Astuti, Retno Fitri; Avoressi, Dian Dianti; Edy, Sarwo; Wicaksono, Ari (CV. Creative Tugu Pena, 2022)
Bekasi Regency is one of the industrial areas in West Java. So various kinds of factories produce various kinds of products. With so many factories in Bekasi Regency, it will lead to a higher level of urbanization or population movement from villages to cities in order to earn a living and change their destiny. From the data obtained, from the Bekasi Regency BPS data in 2015 the population was 72,911 people, in 2016 the population was 92,595, in 2017 the population was 95,316, in 2018 the population was 100,714, and in 2019 the population was 103,535. And over time, the need for housing facilities to support their lives in urban areas will increase. And of course, surely the nomads and natives will start building a family and settle in Bekasi Regency. So the need for health facilities will definitely increase, for example, hospitals. In this case, from the data obtained, the number of RSIA facilities in Bekasi Regency is still minimal, especially in Central Cikarang District which does not have any Hospital facilities or Mother and Child Hospital. Therefore, it is necessary to plan for the procurement of RSIA in Central Cikarang District with a behavior architecture approach. This behavior architecture functions as a bridge to change the mood of building users when they are active in it. This concept can be implemented to building elements such as the concept of tread, interior, material and color. By analyzing the behavior, especially the mother and child, it will create an atmosphere of fun play space inside and outside the building so that the healing process can be faster. And the use of open areas as healing gardens in hospitals is also a solution to be applied in Bekasi Regency, if you look at behavioral architecture. With the addition of this green space, in addition to reducing pollution and excessive heat, it can also have an effect on the patient's healing process. Keywords: Hospital, Mother and Child, Behavior Architecture